Contemporary Trends in the Use and Outcomes of Surgical Treatment of Tricuspid Regurgitation. Issue 12 (22nd December 2017) - Alqahtani, Fahad; Berzingi, Chalak O.; Aljohani, Sami; Hijazi, Mohamad; Al‐Hallak, Ahmad; Alkhouli, Mohamad
Abstract : Background: Tricuspid regurgitation (TR), if untreated, is associated with an adverse impact on long‐term outcomes. In recent years, there has been an increasing enthusiasm about surgical and transcatheter treatment of patients with severe TR. We aim to evaluate the contemporary trends in the use and outcomes of tricuspid valve (TV) surgery for TR using the National Inpatient Sample. Methods and Results: Between January 1, 2003 and December 31, 2014, an estimated 45 477 patients underwent TV surgery for TR in the United States, of whom 15% had isolated TV surgery and 85% had TV surgery concomitant with other cardiac surgery. There was a temporal upward trend to treat sicker patients during the study period. Patients who underwent isolated TV repair or replacement had a distinctly different clinical risk profile than those patients who underwent TV surgery simultaneous with other surgery. Isolated TV replacement was associated with high in‐hospital mortality (10.9%) and high rates of permanent pacemaker implantation (34.1%) and acute kidney injury requiring dialysis (5.5%). Similarly, isolated TV repair was also associated with high in‐hospital mortality (8.1%) and significant rates of permanent pacemaker implantation (10.9%) and new dialysis (4.4%). Isolated TV repair and TV replacement were both associated with protracted hospitalizations and substantial cost. Conclusions: In contemporary practice, surgical treatment of TR remains underused and is associated with high operative morbidity and mortality, prolonged hospitalizations, and considerable cost.